Nepal heritage documentation project, NHDP - Brosius, Christiane; Michaels, Axel (Universität, 2020)
DANAM is the Digital Archive for Nepalese Art and Monuments and the heart of the Nepal Heritage Documentation Project (NHDP), located at the Heidelberg Centre of Transcultural Studies (HCTS) and the Academy of Sciences (AdW) and operated in cooperation with Saraf Foundation and the Department of Archaeology, Nepal. The database offers visual and textual documentation of heritage monuments, which are threatened by urbanisation and natural disasters. Data sets contain structured information on the monuments, i.e. details of their location, history, architectural structure, and religious and social activities. It presents photographs, maps, plans and drawings, transcriptions of inscriptions, and historical and anthropological reports. Descriptions are available in both English and Nepali. References to scholarly documentation and resources enable further research interests to be explored. DANAM is based on Arches (v.4), an open-source, geospatially-enabled software platform for cultural heritage inventory and management, developed jointly by the Getty Conservation Institute and World Monuments Fund. Funded by the British Arcadia Foundation, the entire content of DANAM is is openly accessible to the general public. A large part of the data is also stored in heidICON and heiDATA.